Pragmatic competence in English language learning: Exploring speech act awareness among Jordanian students - Al Mseideen, Ahmad; Yunus, Kamariah Binti; Almahasees, Zakaryia (Research Journal in Advanced Humanities, 2025)
This research examines the pragmatic competence of Jordanian undergraduate students at Applied Science Private University in terms of their comprehension and production of English speech acts, including requests, apologies, complaints, and refusals. The research also investigates the impact of social determinants, that is, power relationships, social distance, and status, on students' selection of communicative strategies. Data were collected through qualitative interviews and Discourse Completion Tests (DCTs). A thematic analysis of the interview data revealed that students possess rudimentary knowledge of pragmatic principles but encounter difficulties with their application, especially in contexts involving politeness and indirectness. The DCTs created a controlled setting to observe how students create speech acts in various social settings, complementing the findings from the interviews. It was found that the language choice of students is gender and discipline-based, with female and humanities students using more indirect language strategies and male technical students using more direct language. The findings reveal a gap in students' ability to adapt language to social contexts, highlighting the need for more explicit instruction in pragmatic competence within English language education. The study contributes to the understanding of pragmatic competence in non-native English speakers and sheds light on how language instruction methods can be improved.